Action plan for harm reduction and good practices in the immunization room: Experience report (Research, Society and Development, 2024)
Objective: To identify inconsistencies in vaccination practices that may result in harm. Methodology: descriptive and exploratory study, of the experience report type, carried out based on publications and observation of practices in the immunization room of a Family Health Unit in the Legal Amazon, based on a technical visit carried out by students during an undergraduate course for the application of a tool and identification of problems and priorities for the proposition of an action plan for improvements. Results: structural and operational failures were identified, such as the absence of Standard Operating Procedure, as well as the lack of regular training for the team. That said, an action plan was presented with interventions for improvements. Final Considerations: the study emphasizes the importance of continuing health education to improve practices in immunization rooms, in addition to ensuring greater safety for users and professionals.